Internment - Ahmed, Samira (Fiction writer) (New York Little, Brown and Company, 2019)
"A terrifying, futuristic United Sates where Muslim-Americans are forced into internment camps, and seventeen-year-old Layla Amin must lead a revolution against complicit silence"--
Includes bibliographical references (pages 385-386)
Keywords: Prejudices -- Juvenile fiction; Muslims -- Juvenile fiction -- United States; Concentration camps -- Juvenile fiction; Revolutionaries -- Juvenile fiction; Prejudices -- Fiction; Muslims -- Fiction -- United States; Concentration camps -- Fiction; Revolutionaries -- Fiction; Science fiction; Science fiction